Generation of a photocontrollable recombinant bovine parainfluenza virus type 3. (22nd January 2023) - Okura, Takashi; Tahara, Maino; Otsuki, Noriyuki; Sato, Moritoshi; Takeuchi, Kaoru; Takeda, Makoto
Abstract: Bovine parainfluenza virus type 3 (BPIV3) is a promising vaccine vector against various respiratory virus infections, including the human PIV3, respiratory syncytial virus, and severe acute respiratory syndrome‐coronavirus 2 infections. In this study, we combined the Magnet system and reverse genetic approach to generate photocontrollable BPIV3. An optically controllable Magnet gene was inserted into the H2 region of the BPIV3 large protein gene, which encodes an RNA‐dependent RNA polymerase. The generated photocontrollable BPIV3 grew in specific regions of the cell sheet only when illuminated with blue light, suggesting that spatiotemporal control can aid in safe clinical applications of BPIV3.